O ensino religioso na visão de alunos, professoras e professoras coordenadoras de escolas públicas estaduais de ensino fundamental ciclo II da cidade de São Paulo: um estudo exploratório - Faria, Vera Regina Aparecida (2006)
This work refers to the research whose objective was to investigate the implementation of Religious Education in the curricular grid of two public middle schools (from 5th to 8th grades) in the city of São Paulo, Brazil, according to the perspective of teachers, school coordinators and students involved in the process. The research aims to obtain new discernment, gather information for the creation of a more precise research problem, and develop hypotheses that would lead to further researches. Despite the fact that Religious Education has had legal basis to be applied at public schools since 1930, this is the first time in the state of São Paulo that History, Social Sciences or Philosophy teachers, all members of São Paulo State Office of Education, have been in charge of the subject. The nature of the research is an exploratory study, with predominantly descriptive data obtained from a direct contact with students, teachers and school coordinators. Two schools from different neighborhoods, regions, districts, and sociocultural and economic contexts were chosen, so that we could observe the similarities and differences in relation to the subjects' manifestations from both schools related to the new proposal from São Paulo State Office of Education. This investigation intends to contribute in order to expand the data in such a troubled trajectory, such as the Religious Education in public schools. The data obtained throughout the year 2005, with the aid of instruments previously built and tested, were mapped, organized and are displayed in summary charts and tables. The results obtained reveal that the school agents are unaware of the Religious Education proposal in some aspects and it is neglected related to its contents and practices. The difficulty in implanting that project is mainly linked to the diversity of situations and the proportions of public schools such as the ones from the state of São Paulo